Flood Hazard Mapping and Evacuation Route Planning Using Geographic Information Systems (GIS) in Malang City, East Java, Indonesia - Muhammad Farid Abdillah; Hendrata Wibisana; Bagas Aryaseta (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Flooding is one of the most frequent hydrometeorological disasters in Indonesia and continues to threaten urban areas due to rapid land-use changes, increasing impervious surfaces, and inadequate drainage systems. Malang City, East Java, has experienced rapid urban development that increases flood susceptibility in several districts. Therefore, identifying flood-prone areas and determining appropriate evacuation routes are essential components of disaster risk reduction.This study aims to identify flood-prone areas and determine optimal flood evacuation routes in Malang City using Geographic Information Systems (GIS). The analysis integrates several physical parameters affecting flood susceptibility, including rainfall, land use, slope, soil type, and topographic conditions. Spatial analysis was conducted through thematic map overlay techniques to produce flood susceptibility zoning. Furthermore, road network analysis was employed to identify the shortest and safest evacuation routes from flood-prone locations to designated evacuation points.The results are expected to provide flood hazard maps classified into several susceptibility levels and evacuation route maps that support emergency response planning. These outputs can serve as references for local governments in improving flood mitigation strategies, spatial planning, and disaster preparedness. The application of GIS demonstrates its capability to integrate spatial datasets for hazard assessment and evacuation planning, providing an effective decision-support system for sustainable urban disaster management.